2020
DOI: 10.3390/foods9081091
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Chemical Composition, Fatty Acid Profile, and Sensory Properties of a Mountain Pecorino Cheese

Abstract: This study aims to assess the compositional traits and sensory characteristics of a traditional pecorino cheese associated with management and feeding system seasonality. The study was carried out on two mountain dairy farms using an outdoor, pasture-based system from April to October (OutS), and an indoor system (InS) during the rest of the year. Outdoor-produced milk had higher fat content and a tendency for protein and somatic cell count to be higher. The OutS cheeses showed higher dry matter and fat conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 66 publications
2
11
1
Order By: Relevance
“…This trend could be due to the fact that, in June, ewes grazed on dry natural pasture and on residues of wheat threshing, which contains wheat grain rich in unsaturated fatty acids—in particular, linoleic acid (precursor of PUFA-ω6) and oleic acid (C18:1) [ 50 ]. As reviewed by different authors, the feeding system plays a major role in modulating the fatty acid composition of cow, goat, and sheep milk [ 50 , 51 , 52 , 53 ]. Milk from animals grazing a native pasture with a higher botanical biodiversity, which occurs in the spring in Mediterranean pastures, contains more CLA and PUFA and less saturated fatty acid and shows a lower PUFA-ω6/PUFA-ω3 ratio than milk sourced from animals fed at stalls [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This trend could be due to the fact that, in June, ewes grazed on dry natural pasture and on residues of wheat threshing, which contains wheat grain rich in unsaturated fatty acids—in particular, linoleic acid (precursor of PUFA-ω6) and oleic acid (C18:1) [ 50 ]. As reviewed by different authors, the feeding system plays a major role in modulating the fatty acid composition of cow, goat, and sheep milk [ 50 , 51 , 52 , 53 ]. Milk from animals grazing a native pasture with a higher botanical biodiversity, which occurs in the spring in Mediterranean pastures, contains more CLA and PUFA and less saturated fatty acid and shows a lower PUFA-ω6/PUFA-ω3 ratio than milk sourced from animals fed at stalls [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-nine percent of the producers indicated that they used milk from their own farms with cows on pasture-based diets. Additionally, most of the producers (60%) also indicated that they did not use any ese cheeses are reported to have different unique characteristics, which could be attributed to different factors such as unique processing techniques, feed type, milk quality, and cow breeds [7,8,19].…”
Section: Resultsmentioning
confidence: 99%
“…Another study observed that feeding grass silage to fattening bulls led to higher C18:3 n-3 in the adipose tissue compared to bulls fed maize silage [75]. The positive effect of dietary grass supplementation on the fatty acid profile of milk and derived products (e.g., cheese) has also been demonstrated in different lactating species such as cows [76], buffalo [77] and ewes [78]. Forage species, cultivar, conservation method and level of inclusion are all sources of variation in the rates and extents of ruminal biohydrogenation of dietary FA from forages as well as their transfer to products [79].…”
Section: Effects On Product Qualitymentioning
confidence: 94%